Pollution potential of solid wastes from the Ergani copper plant - Tumen, F.; Bildik, M.; Boybay, M.; Cici, M.; Solmaz, B. (My University, 1992)
Heavy metals released into the water from converter and reverberatory slags and flotation tailings were traced by utilizing columnar percolation tests for one year. The fixation characteristics of both local and kaolinitic soils accompanying these wastes were explored. The metal contents of water percolated from the wastes in the columns exposed to atmospheric conditions were also examined. In addition heavy metal releasing capability of wastes was determined by utilizing the EPA extraction test to the original samples and their residues of percolation. The converter slag and flotation tailing releasing heavy metals in considerable amounts were found to be the important pollutants. Reverberatory slag is a rather stable waste. The results from EPA extraction tests agreed with those from percolation tests. Heavy metals released from the wastes can be fixed by soils in a significant proportion. -English summary
Ergani Bakir Isletmesi kati atiklarinin kirlilik potansiyeli
Keywords: Diyarbakir; Ergani; Turkey; copper plant; flotation tailings; heavy metal; pollution potential; slag; soil